Children's uses of cultural objects in their life trajectories - Zittoun, Tania (My University, 2008)
In this paper, I reflect upon two case studies of children's progressive mastery of semiotic means, by Srivastava, Budwig and Narashiman (this volume) and Pinto, Accorti and Cameron (this volume). I first highlight their shared mera-theoretical assumptions - primacy of semiosphere, non linearity of development and social origin of psychological processes. I then identify three theoretical issues raised by the case studies and their analysis: the danger of a rigid understanding of socialisation, the possible limits of ternary analyses and the disconnection between analysis of microprocesses of development and of life trajectories. To overcome these issues, I finally propose a midrange model, which highlights the emotional nature of interactions and the sense-making in the construction of semiotic mastery.